2023
DOI: 10.1002/adfm.202212748
|View full text |Cite
|
Sign up to set email alerts
|

Natural Cell Patches: Melanin Nanoparticles for MR Imaging‐Guided Antiatherosclerosis Therapy via Attenuating Macrophage Pyroptosis

Abstract: Pyroptosis, characterized by inflammasome activation, membrane Gasdermin D (GSDMD)-pore formulation, and the rapid release of inflammatory cytokines, can induce plaque instability and atherosclerosis progression. Nevertheless, insights into the precise antiatherosclerosis therapies targeting pyroptosis remain limited. Here, a novel biomedical application of natural polyphenol melanin as a theranostic antipyroptosis defense nanoplatform for atherosclerosis is reported. Ultrasmall melanin nanoparticles are easil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…[234][235][236][237][238] For instance, Zhang et al developed ultrasmall melanin nanoparticles called RpMPs that were functionalized with cRGD peptide to achieve ROS elimination at a molecular level for the treatment of atherosclerotic plaques (Figure 10E). [239] The administration of RpMPs resulted in downregulation of pyroptosis-associated phenotypes and reduced expression of inflammatory cytokines, effectively eliminating ROS within plaque macrophages and inhibiting pyroptosis. The RpMPs-treated group exhibited a higher fluorescence intensity in plaque-bearing aortas compared to the control group, indicating excellent targeting efficiency of RpMPs toward atherosclerotic lesions (Figure 10F).…”
Section: Ros-scavenging For Anti-inflammatory Effectsmentioning
confidence: 99%
“…[234][235][236][237][238] For instance, Zhang et al developed ultrasmall melanin nanoparticles called RpMPs that were functionalized with cRGD peptide to achieve ROS elimination at a molecular level for the treatment of atherosclerotic plaques (Figure 10E). [239] The administration of RpMPs resulted in downregulation of pyroptosis-associated phenotypes and reduced expression of inflammatory cytokines, effectively eliminating ROS within plaque macrophages and inhibiting pyroptosis. The RpMPs-treated group exhibited a higher fluorescence intensity in plaque-bearing aortas compared to the control group, indicating excellent targeting efficiency of RpMPs toward atherosclerotic lesions (Figure 10F).…”
Section: Ros-scavenging For Anti-inflammatory Effectsmentioning
confidence: 99%
“…[ 170 ] Zhang et al reported an anti‐pyroptosis defense nanoplatform that inhibits pyroptosis by scavenging ROS to improve the progression of atherosclerosis. [ 171 ] The preparation of these nanomaterials has created a new way of thinking about the treatment of diseases and a possibility for the future clinical treatment of pyroptosis‐related diseases.…”
Section: Pyroptosis Inhibitors For Non‐neoplastic Disease Therapymentioning
confidence: 99%
“…4,5 Meanwhile, macrophages play a critical role in uptaking the oxidized low density lipoprotein (ox-LDL) to deteriorate into the foam cells, simultaneously releasing various inflammatory factors and then inducing the formation of atherosclerotic plaque. 6,7 Clinical study has found that the foam cell-rich atherosclerotic plaque is prone to rupture into thrombus, inducing some fatal complications such as myocardial infarction and stroke. 8,9 Thence, it is highly important to efficiently recognize the foam cells and then precisely identify the morphology and disperse distribution of the plaques for physicians to make timely clinical decisions and perform proactive interventions as early as possible.…”
Section: Introductionmentioning
confidence: 99%
“…10 Currently, computed tomography (CT), 11 optical coherence tomography (OCT), 12 magnetic resonance imaging (MRI), 13 and ultrasonography (US) 14 are utilized to detect the structural and anatomic features of atherosclerotic plaques. 6 However, these conventional methods always have difficulty in providing the detailed information for atherosclerotic lesions owing to their intrinsically low spatial resolution. 15 Fluorescence imaging has become as an indispensable modality because of its high sensitivity, excellent spatial resolution, and fast acquisition and image processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation